Comorbid Psychiatric Disorders in Children and Adolescents with Nocturnal Enuresis - Amiri, Shahrokh; Shafiee-Kandjani, Ali Reza; Naghinezhad, Roghayeh; Farhang, Sara; Abdi, Salman (Urology Journal, 2017)
Purpose: The present study was conducted with the aim of identifying the frequency of comorbid psychiatricdisorders in children and adolescents with nocturnal enuresis (NE). Materials and Methods: In this descriptive-analytical study, 183 children and adolescents aged 5-18 years withNE referred to psychiatric clinics at Tabriz University of Medical Sciences were selected in 2015. A structuredclinical diagnostic interview, the kiddie-schedule for affective disorders and schizophrenia (K-SADS), was employedbased on the diagnostic and statistical manual of mental disorders (DSM-IV-TR) for the diagnosis of NEand comorbid psychiatric disorders. Results: In this study, 39 participants (21.3%) were female and 144 (78.7%) were male. The mean age of participantswas 8.69 ± 2.34 years. The lifelong incidence of mental disorders among enuretic children and adolescentswas 79.23%. The highest incidence belonged to attention deficit/hyperactivity disorder (ADHD) with 74.9%, oppositional-defiant disorder (ODD) with 53%, and tic disorders with 12% (motor tics together with a single caseof vocal tic). The lowest incidence was for conduct disorder, bipolar affective disorder, and post-traumatic stressdisorder (PTSD) with 5%. Based on the Fisher exact test, there was no significant difference between girls andboys in terms of psychiatric disorders incidence (P > .05). Conclusion: Comorbid psychiatric disorders with NE are common among children and adolescents. Therefore,in-depth examination of other psychiatric disorders needs to be carried out in enuretic children and adolescents,which will affect the treatment and prognosis of NE.